Novel therapeutic strategies for renal graft preservation and their potential impact on the future of clinical transplantation. Issue 4 (August 2019) - Juriasingani, Smriti; Akbari, Masoud; Luke, Patrick; Sener, Alp
Abstract : Purpose of review: The current review aims to examine recent evidence about improvements, therapeutics and novel approaches for renal graft preservation along with presenting a pragmatic outlook on their potential for clinical translation. Recent findings: Modifying established cold preservation methods (4 °C) with oxygenation, gene therapies and gasotransmitters such as hydrogen sulfide has been shown to improve renal graft outcomes with minimum modifications to current protocols. These strategies have also shown promise in the context of normothermic preservation (34–37 °C), which circumvents the damage caused by cold preservation. Although normothermic machine perfusion (NMP) is being evaluated in clinical trials, it is limited by high cost, the use of blood and the lack of standardized protocols. Recent studies confirmed that preservation at subnormothermic temperatures (∼20 °C) is effective with approved preservation solutions and, in conjunction with exogenous hydrogen sulfide therapy, this approach may expedite a static preservation alternative to NMP. Summary: Progress has been made in investigating improvements and alternatives to cold preservation. Promising therapeutic strategies have also been studied in the context of cold, subnormothermic and normothermic preservation. Further research is needed to optimize clinical renal graft preservation.